Discrimination against women in the local labour markets of Eastern Poland - Bolińska, Monika; Dykas, Paweł; Wisła, Rafał (Publishing House of Wroclaw University of Economics and Business, 2023)
This study discusses the effect of spatial factors, understood as distances between counties (Pl. ‘powiat’), on the increase in unemployment rates in Eastern Poland, and also aims to determine the effect of business cycles on unemployment by gender. The research project was based on the methods of spatial econometrics used to analyse panel data collected in the period 2010-2020 in 101 counties in Eastern Poland (NUTS 4). The study led to the conclusion that women needed a longer time to get a job than men in the phase of economic expansion. In times of rising unemployment in the local labour markets of Eastern Poland, women left the workforce at a greater rate than men, and when unemployment in those markets fell, women remained out of work for a longer time.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 177-196
Keywords: spatial econometrics; labour market; regional analyses; product market